DETERMINATION OF THE INCIDENT LEVEL OF CHRONIC VIRAL HEPATITIS AMONG THE POPULATION OF OQDARYO DISTRICT (SAMARKAND REGION) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Viral hepatitisepatitis is an inflammation of the liver that is caused by a variety of infectious viruses and noninfectious agents leading to a range of health problems, some of which can be life threatening. There are five strains of the hepatitis virus, referred to as types A, B, C, D and E. While they all cause liver disease (hepatitis), they differ in important ways including modes of transmission, severity of the illness, geographical distribution and prevention methods. In particular, types B and C lead to chronic disease in hundreds of millions of people and together are the most common cause of liver cirrhosis, liver cancer and viral hepatitis-related deaths.